2008
DOI: 10.1080/01480540701688725
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative, Antioxidant, and Antimutagenic Activities of Flavonoid-Enriched Extracts from (Tunisian)Rhamnus alaternusL.: Combination with the Phytochemical Composition

Abstract: A pronounced antiproliferative effect on human leukemia K562 cells was shown with flavonoid-enriched extracts from Rhamnus alaternus roots and leaves, with, respectively, IC(50) values of 165 and 210.73 microg/mL. High DPPH radical-scavenging activity (7.21 and 18.84 microg/mL, respectively) and antioxidative effects using the xanthine oxidase assay (IC(50) values of 83.33 and 103.96 microg/mL, respectively) were detected in the presence of the two tested extracts. Although no mutagenic effect was observed whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…It has traditionally been used as a digestive, diuretic, laxative, hypotensive and for the treatment of hepatic and dermatological complications (Boukef, 2001). Previous studies have shown potent antioxidant, free radical scavenging, antimutagenic and antigenotoxic activities of crude extracts from R. alaternus (Chevolleau, Debal, & Ucciani, 1992;Ben Ammar et al, 2005, 2007a, 2008a, 2008b. We have also reported others biological activities of R. alaternus extracts: antibacterial and antiproliferative.…”
Section: Introductionmentioning
confidence: 58%
“…It has traditionally been used as a digestive, diuretic, laxative, hypotensive and for the treatment of hepatic and dermatological complications (Boukef, 2001). Previous studies have shown potent antioxidant, free radical scavenging, antimutagenic and antigenotoxic activities of crude extracts from R. alaternus (Chevolleau, Debal, & Ucciani, 1992;Ben Ammar et al, 2005, 2007a, 2008a, 2008b. We have also reported others biological activities of R. alaternus extracts: antibacterial and antiproliferative.…”
Section: Introductionmentioning
confidence: 58%
“…The antiproliferative property of Hemidesmus indicus extract has been reported by earlier investigators (Thabrew et al, 2005). Both coumarins and flavonoids have been attributed to possess antiproliferative properties (Kostova, 2005;Ammar et al, 2008) and may be responsible for the cytotoxic effects exhibited by the root extract of H. indicus.…”
Section: Resultsmentioning
confidence: 86%
“…The high phenolic content of some herbs consumed by Thai people was linked to their antimutagenic potential (Kruawan and Kangsadalampai, 2006). Recently, flavonoid-enriched extracts from Rhamnus alaternus roots and leaves were shown to demonstrate significant protection against sodium azide (Ammar et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The Rhamnus alaternus plant, the so-called "Imlilesse or Safir" in the North of Algeria, has been traditionally used for a long time in various medicine areas as infusion notably for its gastric, hypotensive, purgative, laxative, diuretic, antihypertensive, hepatoprotective, and digestive effects and finally to treat dermatological complications [20]. Such biological activities would be related to the natural presence of beneficial compounds as evidenced by many experimental studies, that pointed out that R. alaternus contains important metabolites-such as flavonoids, coumarins, glycosides, tannins, anthraquinones, and polyphenolic compounds [21,22]. Some of these molecules were isolated from Rhamnus alaternus using various extraction processes (i.e., maceration, decoction, hydrodistil-lation, soxhlet, ultrasonic extraction) and demonstrated various pharmacological properties including antihyperlipidemic, antioxidant, antigenotoxic, antiproliferative, and antimutagenic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these molecules were isolated from Rhamnus alaternus using various extraction processes (i.e., maceration, decoction, hydrodistil-lation, soxhlet, ultrasonic extraction) and demonstrated various pharmacological properties including antihyperlipidemic, antioxidant, antigenotoxic, antiproliferative, and antimutagenic activities. Some biological activities, especially antibacterial and antiproliferative effects were reviewed elsewhere [8,20,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%